Multi‐directional response of unreinforced masonry walls: experimental and computational investigations. (18th February 2016) - Dolatshahi, Kiarash M.; Aref, Amjad J.
Summary: This paper describes the results of an experimental and numerical study that focused on multi‐directional behavior of unreinforced masonry walls and established the requisite of the related proposed design equations. The tests were conducted following several sets of multi‐directional loading combinations imposed on the top plane of the wall along with considering monotonic and cyclic quasi‐static loading protocols. Various boundary conditions, representing possible wall–roof connections, were also considered for different walls to investigate the influence of rotation of the top plane of the wall on the failure modes. The results of the tests were recorded with a host of high precision data acquisition systems, showing three‐dimensional displacements of a grid on the surface of the wall. Finite element models of the walls are developed using the commercial software package ABAQUS/Explicit compiled with a FORTRAN subroutine (VUMAT) written by the authors. The experimental results were then used to validate the finite element models and the developed user‐defined material models. With the utility of validated models, a parametric study was performed on a set of parameters with dominant influence on the behavior of the wall system under in‐plane and out‐of‐plane loading combinations. The experimental and numerical results are finally used to investigate the adequacy of ASCE 41 empirical equations, and some insights and recommendations are made. Copyright © 2016 John Wiley & Sons, Ltd.